Isolation, identification, and optimization of the fibrinolytic protease-producing strains - Umay, Betul; Gul, Abdulkadir; Tanyildizi, Muhammet Saban (Springer Heidelberg, 2023)
Cardiovascular complications due to thrombosis have become one of the main causes of death worldwide. The high cost and undesirable side effects of existing thrombolytic agents have led researchers to isolate potential strains that produce fibrinolytic enzymes for therapeutic applications. Fibrinolytic enzymes, especially of microbial origin, are recognized as potential therapeutic candidates for thrombosis. In this study, isolation, identification, and optimization of fibrinolytic protease enzyme-producing strains were performed using fermentative protein sources. Fibrinolytic protease-producing strains were selected by analyzing the isolated strains on skim milk agar medium. The selected strains were examined on blood agar and fibrin plate medium, and the ones showing high enzymatic activity were determined. The strain determined to have the highest activity was identified as Acinetobacter johnsonii TR01 by 16S rRNA analysis. The maximum fibrinolytic protease production of the strain occurred at 60 degrees C and pH 7.0. Under different medium conditions used for enzyme production, fructose was found to be the best carbon source, while yeast extract and peptone were the best nitrogen sources. It was observed that CaCl2, KH2PO4, and MgSO4 components had a negative effect, while MnCl2 and ZnC4H6O4 components had a positive effect on enzyme production. The medium composition for maximum enzyme activity (8.30 IU/ml) determined by Response Surface Methodology was 14.22 g/L fructose, 11.190 g/L yeast extract, 14.22 g/L peptone, 0.5 g/L MnCl2, and 0.5 g/L ZnC4H6O4.
Keywords: Thrombosis; Therapeutic applications; Fibrinolytic protease; Strain isolation